PAPARAN HIDROGEN SULFIDA DI LINGKUNGAN KERJA STUDI KASUS PADA PEKERJA PT. PERTAMINA HULU MAHAKAM - Mulya, Widya Mulya (Program Studi Kesehatan dan Keselamatan Kerja, 2019)
Hydrogen sulfide is an irritant for the lungs, classified as an asphyxiant because the main effect is to paralyze the respiratory centre (Soemirat 2003). The North Processing Unit (NPU) is a facility owned by PT. Pertamina Hulu Mahakam, Oily Water Treatment Platform (OWTP) is one part of the NPU process, flotator unit on the 29 October 2017 showed the value of hydrogen sulfide concentration of 14 ppm ( threshold value of 1 ppm, Permenakertrans Nomor PER. 13/MEN/X/2011). The purpose of the study was to find out hydrogen sulfide exposure in the work environment of case studies on PT. Pertamina Hulu Mahakam workers. This is done by giving a hydrogen sulfide related questionnaire. Based on the measurement data on the 22 June 2018, flotator unit of 7 ppm. Based on the calculation results, workers who smell hydrogen sulfide in the OWTP work area are 86,7% in the low- risk category, workers who are disturbed by the smell of hydrogen sulfide is 73,3% in the medium risk category, workers with painful eye complaints/ watery eyes/ cough of 56,7% in the low-risk category and 43,4% in the medium risk category, the level of knowledge of hydrogen sulfide workers was 76,7% in the good category.